2022
DOI: 10.1007/s00405-021-07221-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of Glut-1 and H+/K+-ATPase expression in hyperplasia of mice laryngeal epithelium induced by pepsin

Abstract: Purpose To explore the role played by Glut-1 and H+/K+-ATPase in pepsin-induced, mouse laryngeal epithelial proliferation, growth, and development. Methods We established a mouse model of laryngopharyngeal reflux and measured Glut-1 and H+/K+-ATPase expression levels in mouse laryngeal epithelium treated with artificial gastric juice containing pepsin. Results Artificial pepsin-containing gastric juice induced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 30 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…Moreover, pepsin enhanced the expression of H + /K + ATPase in the abovementioned 3-dimensional culture system, as well as in mouse laryngeal epithelial cells. 3,13 These results suggest that acidified pepsin interacts with H + /K + ATPase during the progression of VCL.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Moreover, pepsin enhanced the expression of H + /K + ATPase in the abovementioned 3-dimensional culture system, as well as in mouse laryngeal epithelial cells. 3,13 These results suggest that acidified pepsin interacts with H + /K + ATPase during the progression of VCL.…”
mentioning
confidence: 75%
“…13 We demonstrated that acidic pepsin significantly increased migration and proliferation in those cells in a 3-dimensional culture system using primary VCL cells. 3 These results suggest that pepsin plays an important role in the abnormal proliferation of leukocytes observed in VCL. We also demonstrated that the expression of H + /K + ATPase, which is responsible for gastric acid secretion, was elevated in VCL and laryngeal carcinoma.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Ao et al . reported that long-term administration of pepsin to larynx led to hyperplasia of mice laryngeal epithelium [ 11 ]. In this study, pepsin content increased in VFL with the increase in the grade of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Pepsin can reportedly enhance the epithelial–mesenchymal transformation of laryngeal cancer cells and also promote the migration and clonogenic ability of hypopharyngeal cancer cells, contributing to the progression of laryngeal and hypopharyngeal cancers, respectively [ 9 , 10 ]. Ao et alrecently reported that long term administration of artificial pepsin-containing gastric juice to larynx induced hyperplasia of the laryngeal epithelium in normal mice [ 11 ]. Furthermore, the content of pepsin in VFL tissues has been found to be significantly higher than that in normal vocal fold tissues [ 12 ].…”
Section: Introductionmentioning
confidence: 99%